Disposable Retrieval Bag Significantly Reduces Surgical Site Infections After Laparoscopic Appendectomy: A Retrospective Analysis - Abdussalam Mohamed Hounki; Aiesh Imbarek Hassan; Nouh Amar Alshetwy; Karima Alfitory Ahmed (African Journal of Advanced Pure and Applied Sciences, 2025)
Although laparoscopic appendectomy (LA) is widely accepted for its clinical benefits, postoperative infectious complications remain a concern. There is limited evidence on the factors that influence surgical site infections (SSIs) after LA, particularly the use of specimen retrieval devices. Patients and Methods: This retrospective analysis comprised 120 individuals who had undergone LA throughout a year. Patients were separated into two groups: Group A utilised a Disposable retrieval bag, while Group B did not use a retrieval bag. Demographic variables, operation length, hospital stay, and postoperative infection problems were statistically evaluated and compared. Results: Both groups had similar appendicitis severity: 27 cases (45%) of acute catarrhal appendicitis, 20 cases (33.3%) of suppurative appendicitis, and 13 cases (21.7%) of perforated appendicitis (P = 1.0). The median age in Group A was 21 years (range: 16-49), whereas Group B had a median age of 25 years (range: 18-56) (P = 0.053). Group A included 60 patients (35 men, 25 females), whereas Group B had 60 patients (32 males, 28 females) (P = 0.071). The average operating time in Group A was marginally shorter (55.7 minutes) than in Group B (57.0 minutes) (P = 0.0231). Superficial wound infections were reported in 1 patient (1.7%) in Group A and 8 patients (13.3%) in Group B (P = 0.007). Intra-abdominal abscesses occurred in two patients (3.3%) in Group B but none in Group A (P = 0.005). The average hospital stay in Group A was substantially shorter (1.6 days) than in Group B (2.7 days) (P = 0.05). Conclusions: Using Disposable retrieval bag during laparoscopic appendectomy greatly lowers operative site infections and intra-abdominal abscesses. It also offers a cost-effective and safe solution without extending the operating time.